Odpowiedź :
Zad 1
7x - 21 - 4 = 2x
5x = 25
x = 5 TAK
Zad 2
x2 = 4x - 4
x2 -4x + 4 = 0
(x-2)^2 = 0
x - 2 = 0
x = 2
Odp b
Zad 3
12x - 12 - 14 = 2
12x = 28
x = 7/3 NIE
5 - 4(x+3) = 15
5 - 4x -12 = 15
-4x = 22
x = -11/2 NIE
1 - (5-3x) = x
1 - 5 + 3x = x
2x = 4
x = 2 TAK
6(2x - 3) = 3(2x - 2)
12x - 18 = 6x - 6
6x = 12
x = 2 TAK
7x - 21 - 4 = 2x
5x = 25
x = 5 TAK
Zad 2
x2 = 4x - 4
x2 -4x + 4 = 0
(x-2)^2 = 0
x - 2 = 0
x = 2
Odp b
Zad 3
12x - 12 - 14 = 2
12x = 28
x = 7/3 NIE
5 - 4(x+3) = 15
5 - 4x -12 = 15
-4x = 22
x = -11/2 NIE
1 - (5-3x) = x
1 - 5 + 3x = x
2x = 4
x = 2 TAK
6(2x - 3) = 3(2x - 2)
12x - 18 = 6x - 6
6x = 12
x = 2 TAK